Study of selected birth defects among American Indian/Alaska Native population: A multi‐state population‐based retrospective study, 1999–2007. Issue 19 (6th November 2018) - Marengo, Lisa K.; Flood, Timothy J.; Ethen, Mary K.; Kirby, Russell S.; Fisher, Sarah; Copeland, Glenn; Meyer, Robert E.; Dunn, Julie; Canfield, Mark A.; Anderson, Tom; Yazzie, Del; Mai, Cara T.; et al.
Abstract : Background: Higher prevalence of selected birth defects has been reported among American Indian/Alaska Native (AI/AN) newborns. We examine whether known risk factors for birth defects explain the higher prevalence observed for selected birth defects among this population. Methods: Data from 12 population‐based birth defects surveillance systems, covering a birth population of 11 million from 1999 to 2007, were used to examine prevalence of birth defects that have previously been reported to have elevated prevalence among AI/ANs. Prevalence ratios (PRs) were calculated for non‐Hispanic AI/ANs and any AI/ANs (regardless of Hispanic ethnicity), adjusting for maternal age, education, diabetes, and smoking, as well as type of case‐finding ascertainment surveillance system. Results: After adjustment, the birth prevalence of two of seven birth defects remained significantly elevated among AI/ANs compared to non‐Hispanic whites (NHWs): anotia/microtia was almost threefold higher, and cleft lip +/− cleft palate was almost 70% higher compared to NHWs. Excluding AI/AN subjects who were also Hispanic had only a negligible impact on adjusted PRs. Conclusions: Additional covariates accounted for some of the elevated birth defect prevalences among AI/ANs compared to NHWs. Exclusion of Hispanic ethnicity from the AI/AN category had little impact on birth defects prevalences in AI/ANs. NHWs serve as a viable comparison group for analysis. Birth defects among AI/ANs require additional scrutiny to identify modifiable risk and protective factors.